Exposure to trichloroethylene III. Psychological functions. - Gamberale, Francesco; Annwall, Görell; Olson, Birgitta Anshelm (Scandinavian Journal of Work, Environment & Health, 1976)
The effect of exposure to the solvent trichloroethylene (TRI) on the performance of tests of numerical ability, reaction time (simple and choice), and short-term memory was studied in 15 healthy male subjects. The subjects were tested individually on three different occasions during exposure to 540 and 1,080 mg/m3). of TRI in inspiratory air and under control conditions, respectively. At predetermined times during the three 70-min exposure periods, samples were taken of the subjects` alveolar air. Neither the reaction time tests nor the short-term memory test showed any signs of performance decrement during exposure to TRI as compared to those administered under control conditions. However, a statistically significant decrement in performance was obtained on the test of numerical ability during exposure to TRI. The results as a whole indicate that there should not be any risk of an acute effect on central nervous functions at concentrations which do not considerably exceed the Swedish threshold limit value for the solvent (160 mg/m3).
Keywords: behavioral effect; experimental psychology; exposure; psychological function; trichloroethylene